Analysis of Heavy Metals in Shellfish, Sediment, and Waters in Seagrass beds Ecosystem in Selangan Village, Bontang City - Akhir, Fatmy Yaumil; Suyatna, Iwan; Pagoray, Henny; Sukarti, Komasanah; Ramang, Muhammad Syahrir; Fitriyana, Fitriyana (Torani Journal of Fisheries and Marine Science, 2023)
Selangan Hamlet is a water area in Bontang City where community activities are very active. Bontang City is an area that has a high utilization of coastal areas such as tourism, cultivation, trade, sea transportation services, and industrial areas. The impact of the industrial area on these waters is the contamination of these waters with heavy metals which will have an impact on aquatic organisms and the surrounding community who ultiize these waters. The purpose of this study was to identify the content of heavy metals lead (Pb), copper (Cu), magnesium (Mg), iron (Fe), and mercury (Hg). This research was conducted in January-June 2023 in Bontang waters, Selangan Hamlet. Sampling involyes analyzing water quality and testing heavy metals such as Cu, Pb, Fe, Mg, and Hg. The samples to be analyzed are water, sediment, seagrass and blood clams. The results of the analysis obtained in these waters, at the four stations, namely the south, east, west and north stations. At all stations in the heavy metal test Cu, Pb, Fe, Mg and Hg heavy metal content is only found in blood clams (Anadara granosa). In water, sediment and seagrass, the values obtained are still in normal conditions.